Pengaruh Suasana Toko/Kedai dan Kualitas Pelayanan terhadap Kepuasan Pelanggan Masakan Ayam Penyet Cabe Hijau - Oriza Silva Wijaya; M. Yamin Siregar; Wan Rizca Amelia (Economics, Business and Management Science Journal, 2021)
The research aims to find out "the influence of shop atmosphere and quality of service toward customer satisfaction Resto Chicken Penyet Chili Green Medan". This type of research is associative which is a research that is asking relations between two variables. The population in this study is Resto chicken Penyet chili Green Medan.. A total of 3000 customers and using the Slovin formula with significance level 0.1, the number of samples in this study as many as 96 respondents were taken from some customers. Based on the results of T test and F test, the atmosphere of the shop and the quality of service both partially and simultaneously influence positively and significantly to customer satisfaction variables. It obtained the R Square value of 0.485 so that the figure indicates that a 48.5% customer satisfaction (Y) can be explained by the shop's mood factor (X1) and the quality of Service (X2). The remaining 51.5% is influenced by other factors not described in this study.